ВЛИЯНИЕ МЕСТА ПРОЖИВАНИЯ И ЭТНИЧЕСКОЙ ПРИНАДЛЕЖНОСТИ ИНДИВИДА НА СТРУКТУРУ СУБЛЕКСИКОНА: (на примере реализации тематической группы «Природа» в лексиконе татар Пермского края) (Филолошки студии, 2019)
The influence of the domicile and the ethnicity on the structure of sublexicon (on the material of the thematic group "The Nature" realization in the Perm Tatars lexicon). The article examines the influence of living conditions (city or village) and person’s ethnicity on the structure of sublexicon "The Nature". As it is known, world conceptualization has ethnically limited field, but has not been considered, that the factor "Domicile" influences on the national picture of the world. Further, the Perm region Tatars’ national picture of the world was not previously been the subject of the linguistic consideration. It was shown that the core of sublexicon (that consists of the groups with the largest vocabulary) is solid for the Tatars – city dwellers and villagers and includes the categories: "Phenomena and the elements," "Domestic animals" and "Wild animals". In addition, the units of these groups can be considered models for the respective categories. Groups with a small vocabulary can be taken into account as sublexicon periphery and are exposed to the factor "Domicile": the villagers gave as the considerably more active subgroups "Wild plants" and "Wild Birds", that is explained by a good acquaintance with the relevant realities. City dwellers also showed the predominance of the subgroups "Landscape" and "Resources". In general, research of the frequency characteristics of the subgroups (vocabulary, lexicon and density) reveals the core of the national sublexicon, and qualitative analysis and the identification of common units in sublexicons can detect the standard content of the categories.